2007
DOI: 10.1152/ajpheart.00980.2006
|View full text |Cite
|
Sign up to set email alerts
|

Pregnancy prevents hypertensive remodeling and decreases myogenic reactivity in posterior cerebral arteries from Dahl salt-sensitive rats: a role in eclampsia?

Abstract: Aukes AM, Vitullo L, Zeeman GG, Cipolla MJ. Pregnancy prevents hypertensive remodeling and decreases myogenic reactivity in posterior cerebral arteries from Dahl salt-sensitive rats: a role in eclampsia? Am J Physiol Heart Circ Physiol 292: H1071-H1076, 2007. First published October 20, 2006; doi:10.1152 doi:10. /ajpheart.00980.2006ous studies have demonstrated that pregnancy prevents protective hypertension-induced remodeling of cerebral arteries using nitric oxide synthase (NOS) inhibition to raise mean arte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
33
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(37 citation statements)
references
References 36 publications
3
33
1
Order By: Relevance
“…76 Interestingly, it appears that pregnancy has a trophic effect on perivascular innervation of cerebral pial vessels (Figure 3). Aukes et al 88 used a panneuronal stain to show that perivascular innervation of posterior cerebral arteries was increased during pregnancy in the Dahl saltsensitive rat. Because specific neurotransmitters were not quantified, it is not clear what consequence, if any, this finding might have.…”
Section: Perivascular Innervationmentioning
confidence: 99%
See 1 more Smart Citation
“…76 Interestingly, it appears that pregnancy has a trophic effect on perivascular innervation of cerebral pial vessels (Figure 3). Aukes et al 88 used a panneuronal stain to show that perivascular innervation of posterior cerebral arteries was increased during pregnancy in the Dahl saltsensitive rat. Because specific neurotransmitters were not quantified, it is not clear what consequence, if any, this finding might have.…”
Section: Perivascular Innervationmentioning
confidence: 99%
“…A study that used Dahl salt-sensitive rats made hypertensive by feeding a high-salt diet for the last half of pregnancy (2 weeks) also found that only the nonpregnant rats (treated for the same time period) underwent remodeling, that is, the pregnant animals lacked any structural response to hypertension. 88 The mechanism by which pregnancy prevents hypertensive remodeling of cerebral arteries is not known but appears to be related to the pregnant state. Furthermore, the consequence of pregnancy preventing hypertensive remodeling of cerebral arteries is not clear but may promote forced dilatation at lower pressures and limit the rightward shift in the autoregulatory curve that would normally occur in response to this duration of hypertension.…”
Section: Cerebrovascular Remodeling During Hypertension In Pregnancymentioning
confidence: 99%
“…Pregnancy has direct effects on perivascular innervations by mechanisms not yet elucidated, particularly in pial vessels, in which nerves hypertrophy is produced [15]. This suggests that neurotransmitters may have a role in hypertensive intolerance that results in the genesis of PRES.…”
Section: Discussionmentioning
confidence: 99%
“…The proximal occlusion cuff (O-cuff) constricts the tail artery while the distal VPR cuff measures the change in tail artery volume when blood flow resumes as the O-cuff deflates. This system has been validated in a number of studies [14,15,17] . These measurements were performed in a room maintained at 31 °C so as to ensure adequate blood flow through the tail to improve the signal at the VPR transducer.…”
Section: Experimental Designmentioning
confidence: 99%
“…In recent years, a new technique for measuring blood pressure in conscious rats using a volume pressure recording system has been validated in a number of studies [14,15] . Longterm oral administration of (±)doxazosin (8 mg/kg for 12 weeks) in the rat was also reported in a study by Yono et al [16] .…”
Section: Introductionmentioning
confidence: 99%